Human Sacrifice in Jewish and Christian Tradition. - Karin Finsterbusch; Armin Lange (Numen Book Series, 2006)
This volume asks to which extent ancient practices and traditions of human sacrifice are reflected in medieval and modern Judeo-Christian times. The first part of the volume, on antiquity, focuses on rituals of human sacrifice and polemics against it, as well as on transformations of human sacrifice in the Israelite-Jewish and Christian cultures, while the Ancient Near East and ancient Greece are not excluded. The second part of the volume, on medieval and modern times, discusses human sacrifice in Jewish and Christian traditions as well as the debates about euthanasia and death penalty in the Western world.